Acutely developing, spurious anaemia without actual blood loss. A paradigmatic case report - Lippi, Giuseppe (Biochem Med (Zagreb), 2017)
We describe the case of a 55-year old women admitted at night to the emergency department (ED), complaining for acute abdominal pain lasting for nearly 5 hours. A first blood testing, performed immediately after admission, revealed mild anaemia. A second blood sample, drawn two hours after admission, revealed a considerable decrease of haemoglobin, haematocrit, total white blood cell and platelet counts (between 10-15% reduction). Abdominal ultrasonography was normal and the patient had no signs or symptoms of internal or external haemorrhage. Pre-analytical and analytical errors were accurately excluded. No infusion therapy was administered. After thoughtful discussing the sequence of events, it was ascertained that the first set of blood samples was drawn with the patient in seated position, immediately after ED admission (i.e., approximately 1 min passed from standing to seated position before venipuncture), whereas the second set of blood samples was drawn with the patient lying for two hours in supine position. This case report highlights the importance of standardizing patient position before venous blood collection, along with the crucial role played by cooperation and communication between laboratory and clinical wards for identifying and troubleshooting potential causes of spurious results of in vitro diagnostic testing.